(untitled) (The Conference Hub, 2025)
This article examines the methodological issues involved in studying the history of Uzbekistan within the framework of modern historiography. The research emphasizes that historical knowledge is not merely a collection of facts but a complex, multi-layered socio-cultural process that requires a solid methodological foundation. Special attention is paid to the role of methodology in ensuring the scientific rigor, objectivity, and reliability of historical research. The article analyzes key methodological principles such as historicism, objectivity, critical thinking, and periodization, highlighting their significance in interpreting historical processes within their specific social, political, and cultural contexts.